Fog collection variability in the Andean Mountain Range of southern Colombia - Molina, José M., author; Escobar, Concepción M., author; Gesellschaft für Erdkunde zu Berlin, publisher (Colorado State University. Libraries, 2008)
The spatial and temporal fog collection variability and the potential use of fog as an alternative source of water supply were evaluated in southern Colombia by means of fog collection experiments. Twelve Standard Fog Collectors (SFC) were installed in a mountainous zone, based on topographic and fog formation conditions. Different shade coefficients were evaluated, ranging from 1,680 to 1,850 m a.s.l. Results indicate a high potential for the use of fog to meet water requirements in rural areas. Data collection and analyses covered both dry and rainy seasons. Annual average collection rates amounted to 4.2 l per m2 per day for precipitation + fog, and 3.3 l per m2 per day for fog only. The most important month for collection was June with 5.3 l per m2 per day for precipitation + fog, and 5.0 l per m2 per day for fog only in dry days.
Variabilität der Nebelwassersammlung in den südlichen kolumbianischen Anden
Keywords: fog collection; polypropylene mesh; fog variability; rural water supply; Atrapanieblas; Colombia